2019
DOI: 10.1177/0363546519866452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Risky Pathoanatomy and Demographic Factors on Clinical Outcomes After Isolated Medial Patellofemoral Ligament Reconstruction: A Regression Analysis

Abstract: Background: Multiple studies have demonstrated that a number of demographic and pathoanatomic characteristics are associated with patellofemoral instability, recurrence of instability, and less satisfactory results following medial patellofemoral ligament reconstruction (MPFL-R). Despite the growing volume of research, the relationship of risk factors to patient-reported outcome after MPFL-R is unclear. Purpose: To determine if certain pathoanatomic and demographic factors predict disease-specific quality-of-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 43 publications
2
50
0
2
Order By: Relevance
“…12 Commonly cited clinical thresholds for bony procedures include a TT-TG distance of greater than 16 mm or a CD index of greater than 1.2; however, the original surgical "a la carte menu" that established these criteria predates the surgical option of MPFL reconstruction. 8 There are few outcome studies of MPFL reconstruction evaluating the influence of TT-TG distance and patella alta on isolated MPFL reconstruction; however, several recent retrospective cohort studies 4,10,15,18,24 have demonstrated little influence of TT-TG distance and moderate patella alta on the outcomes of MPFL reconstruction. These studies suggest that isolated MPFL reconstruction can be successful in cases with a higher CD index and TT-TG distance than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…12 Commonly cited clinical thresholds for bony procedures include a TT-TG distance of greater than 16 mm or a CD index of greater than 1.2; however, the original surgical "a la carte menu" that established these criteria predates the surgical option of MPFL reconstruction. 8 There are few outcome studies of MPFL reconstruction evaluating the influence of TT-TG distance and patella alta on isolated MPFL reconstruction; however, several recent retrospective cohort studies 4,10,15,18,24 have demonstrated little influence of TT-TG distance and moderate patella alta on the outcomes of MPFL reconstruction. These studies suggest that isolated MPFL reconstruction can be successful in cases with a higher CD index and TT-TG distance than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…31 In particular, the incidence of femoral tunnel malpositioning has been reported to range from 31% to 67%. 10,37 Although previous studies were inconclusive regarding the effect of and correlation between poor femoral tunnel malpositioning and clinical outcome scores, 23,37 a recent investigation by Hiemstra et al 18 confirmed that femoral tunnel positioning >10 mm from the Schöttle point correlates with lower postoperative BPII 2.0 scores. These findings are in accordance with the results obtained in this study, in which femoral tunnel malpositioning was found in 75% of the patients with a postoperative knee flexion deficit and in 27% of patients who experienced patellar redislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging data were obtained for all patients in the study group and the control group, as were routine radiographs, including standing long leg axis and true lateral view of the knee joint with ≤3 mm of overlap between the femoral condyles. 18 Data were evaluated for the following: severity of trochlear dysplasia (absent, low grade [Dejour type A], or high grade [Dejour type B-D]) 11 ; patellar height, with Caton-Deschamps index ≥1.2 recorded as elevated 9 ; tibial tuberosity–trochlear groove (TT-TG) distance, with >16 mm recorded as elevated 2 ; tibial tuberosity–posterior cruciate ligament (TT-PCL) distance, with >24 mm recorded as elevated 36 ; and varus-valgus alignment. 22 Femoral tunnel accuracy was measured from the center of the tunnel to the center of the Schöttle point, with an increment of 10 mm indicating malpositioning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations